Overview Motivasi Belajar Pendidikan Agama Islam: Analisis Menggunakan Bibliometrik - Nofmiyati Nofmiyati; Miftahuddin Miftahuddin; Darmawati Darmawati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Motivation is closely related to the individual's self; positive motivation will give birth to positive things, as well as vice versa. Learning motivation can change one's mindset, success, and interest. Whereas in Islamic religious education, learning motivation is more closely related to religion. The purpose of this study was to look at the motivation for learning Islamic education using bibliometric analysis of years, keywords, and countries. While the method used was searching for data from Scopus with the keywords